THE EFFECT OF PRACTICUM METHODS ON SCIENCE LEARNING OUTCOMES IN GRADE VIII OF 1st KOTO KAMPAR HULU JUNIOR HIGH SCHOOL - Putriani, Ilah; Sari, Monica Prima (Department of Science Education, 2024)
This study aims to determine the improvement of students in class VIII learning outcomes in Junior High School 1 Koto Kampar Hulu through the implementation of the practicum method. The type of this research was a quasi-experiment with the research design post-test only control group design. Data collection was conducted using the multiple-choice test. Data collection was analyzed using inferential statistics to obtain average scores of student learning outcomes in the control class of 67.14 and experiment class 77.86. Hypothesis testing uses the t-test, and the results show that the null hypothesis is rejected, and the alternative hypothesis is accepted which indicates that there is an effect on the implementation of practicum methods, with an effect size value of 0.84 with a large category indicating that there is a major influence. From the results of this study, it can be concluded that learning science using the practicum method can improve student learning outcomes in class VIII at Junior High School 1 Koto Kampar Hulu